Manufacture of dahi from skim milk adding mango juice (Bangladesh Journal of Animal Science, 2014)
The aim of this research was to prepare and evaluate the quality of dahi using skim milk fortified with 5, 10 and 15 percent of mango juice. The quality of prepared dahi was measured by organolaptic, chemical and microbiological tests. Significant difference was observed within the smell and taste score (p